Analisis Yuridis Terhadap Kasus Ilegal Logging Berdasarkan UU No. 32 Tahun 2009 - Marsha Firstya Alexandra (Universitas Palangka Raya, 2024)
This study employs normative legal methods to evaluate the case of illegal logging involving Munsiram, Defendant Marno Bin Junaidi, and other parties in the Central Java region. The analysis reveals that their actions violate the law and environmental protection principles. Through the examination of court decision Number 379/Pid.B/LH/2023/PN TJK, it is evident that the court applied the key principles outlined in Law No. 32 of 2009 on Environmental Protection and Management. Additionally, this research identifies the contributing factors to illegal logging, such as infrastructure issues, low-quality human resources, and involvement of authorities. Recommended measures to address this issue include strengthening law enforcement, empowering communities, increasing transparency, and developing economic alternatives. In conclusion, firm and sustainable law enforcement is necessary to tackle illegal logging and protect the environment.